1997
DOI: 10.1021/np9702852
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of Fijian Plants. 13. Floribundal, a Nonglycosidic Bisiridoid, and Six Novel Fatty Esters of δ-Amyrin from Scaevola floribunda

Abstract: Floribundal (1), the first example of a nonglycosidic bisiridoid has been isolated from the heartwood of Scaevola floribunda and its structure and relative stereochemistry determined by NMR spectroscopy and molecular modeling. The aglycon 2 of loganin was also isolated. A mixture of six novel δ-amyrin fatty esters with C20−C30 acid moieties (7−12) were isolated from the bark of S. floribunda and their structures elucidated by NMR and HRMS of the parent compounds and their hydrolysis products. The bark also con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…[21,22] The pentacyclic triterpenoids isolated from various species of Goodeniaceae include ursolic acid (oleanene) [23] , myricadiol and taraxerol (taraxerenes), [24] betulin and betulinic acid (lupenes). [25] These compounds and their many derivatives are variously described as being anti-tumorigenic [26] or antidiabetic. [27] Also noted is the anti-tumour activity of the α-bisabolol derivative isolated from Scaevola spinescens and named scaevolal in deference to its relative abundance in the lipophilic plant extracts.…”
Section: Goodeniaceaementioning
confidence: 99%
“…[21,22] The pentacyclic triterpenoids isolated from various species of Goodeniaceae include ursolic acid (oleanene) [23] , myricadiol and taraxerol (taraxerenes), [24] betulin and betulinic acid (lupenes). [25] These compounds and their many derivatives are variously described as being anti-tumorigenic [26] or antidiabetic. [27] Also noted is the anti-tumour activity of the α-bisabolol derivative isolated from Scaevola spinescens and named scaevolal in deference to its relative abundance in the lipophilic plant extracts.…”
Section: Goodeniaceaementioning
confidence: 99%
“…Members of the family are either herbs or shrubs. The family is characterized by the presence of some important phytoconstituents: coumarins [4], iridoid glycosides [5], pentacyclic triterpenoids: myricadiol and taraxerol, betulin and betulinic acid [6] moreover, inulin [7]. Based on recent research, these compounds were found to exhibit various biological activities of medical importance to treat many diseases [8].…”
Section: Introductionmentioning
confidence: 99%